Controlled synthesis of hierarchically crossed metal oxide nanosheet arrays for diesel soot elimination. Issue 61 (5th July 2017) - Ma, Aijing; Gu, Liu; Zhu, Yingming; Meng, Ming; Gui, Jianzhou; Yu, Yifu; Zhang, Bin
Abstract : We propose a facile and versatile strategy to fabricate hierarchically crossed metal oxide nanosheet arrays with high soot elimination activities. Abstract : We propose a facile and versatile strategy for the fabrication of a hierarchically crossed metal oxide nanosheet array on a monolithic FeO x substrate. This strategy can also be extended to synthesize a composite metal oxide nanosheet array, in which the composition can be easily modulated. The as-obtained hierarchically crossed metal oxide nanosheet array exhibited high catalytic activities for diesel soot elimination owing to the enhanced contact efficiency between soot particulates and macroporous catalysts.